Real interpolation of weighted tent spaces. Issue 11 (1st November 2016) - Cao, Jun; Chang, Der-Chen; Fu, Zunwei; Yang, Dachun
Abstract : Let and be a Muckenhoupt weight. In this article, the authors study the real interpolation of the weighted tent space . For all, , and, the authors show that, where and denotes the weighted Lorentz-tent space, which is introduced in this article. As an application, the authors prove a real interpolation result on the weighted Hardy spaces for all and, which, when, seals a gap existing in the original proof of a corresponding result of Fefferman et al. [Trans. Amer. Math. Soc. 1974;191:75–81].